A transitividade na conversação: uma abordagem funcional centrada no uso - Lima, Lucia Chaves de Oliveira (2013)
This work investigates the phenomenon of transitivity in the conversation. We examined the behavior of complements in Brazilian Portuguese speech, and then compared the results with previous researches in the English language by Thompson and Hopper (2001) and in the Spanish language by Vázques (2004). In Brazil, there are no researches that treat this phenomenon in the discursive conversation, for that reason it justifies and reveals the importance of this research that aims to answer questions related to the transitivity of ordinary conversations. Thus, we describe, explain and analize the transitivity based on concrete linguistic data, provided by native speakers of Portuguese language, specifically, spontaneous talk of people from Natal-RN. We have used as theoretical assumptions the Functional Linguistics usage-based (LFCU), which gathers academics of North-American Functional Linguistics, inspired by Chafe (1979), Hopper and Thompson (1980), Thompson and Hopper (2001), Givón (2001), Bybee (2010), Traugott (2009, 2011), among others, as well as Cognitive Linguistics, presented by Langacker (1987), Taylor (1995), Tomasello (1998) and Goldberg(1995), among others. This data consists in conversations extracted from the corpus Banco Conversacional de Natal (FURTADO DA CUNHA). The results obtained from this work confirm the assertions defined by prior conducted studies on the transitivity in the conversation. The research showed that these three idioms, Spanish, Portuguese and English, despite the differences, they present a uniform behavior regarding their transitivity in the conversation. We intend, by this work, to contribute, in some way, to the comprehension of the focused linguistic phenomenon, likewise to build a finer scenario around of the transitivity in the Brasilian Portuguese